Effect of Nonlinear Soil Model on Seismic Response of Slopes Composed of Granular Soil - Yonghee Lee; Hak-Sung Kim; Muhammad Irslan Khalid; Yonggook Lee; Duhee Park (Advances in Civil Engineering)
A series of two-dimensional finite element analyses are performed to simulate the seismic response of slope composed of granular soil. Four sets of input parameters for the nonlinear soil model are used to fit the reference the shear modulus reduction and damping curves, thereby to evaluate the influence of the nonlinear soil model. The first set is fitted to the shear modulus reduction curve. The second and third sets are fitted simultaneously to both shear modulus reduction and damping curves. The final set applied the shear strength adjustment to adequately capture the nonlinear soil response at large strains. The accuracy of each set of parameters are evaluated through comparison with centrifuge model test measurements. It is observed that the nonlinear soil model has a marginal influence on the acceleration response. On the contrary, the vertical settlement is highly influenced by the nonlinear soil model. The discrepancy is shown to increase with an increase in the intensity of the input ground motion. It is demonstrated that the adjustment for the shear strength is important in performing seismic analyses of slopes, which is most often ignored in practice. Based on the results, practical guidelines on how to select the parameters for the nonlinear soil model are provided.